Wine Aging Technologies - Nevares, Ignacio (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Wine aging is a desirable and valuable process, commonly used to improve wine quality, and traditionally carried out in oak wooden casks. The correct use of oak barrels and the ever-increasing demand for barrels in the different production areas of the world has led to a constant search for technological alternatives to reproduce the chemical and physical processes undergone by wines during their stay in barrels.The aim of this Special Issue is to publish a compilation of original research and revision works that cover different aspects of the ageing processes of wine in casks and other alternative systems that reproduce, with different technologies, the transformations that take place in the barrel.Important aspects to be addressed are:the type of technological solutions that exist for wine agingthe impact of these new technologies on the final productcomparison of the effect of emerging and traditional technologies on the wine ageddifferentiation of wines undergoing different systems to avoid fraudcharacterization of the new materials used in barrel productionaccelerated aging of wines with wood and oxygen